The Integration of PAI Teachers’ Competence and Inclusive Learning Strategies to Overcome Students’ Learning Barriers at SMA Negeri 1 Manyak Payed - Fauziah Fauziah; Amiruddin Amiruddin; Lathifah Hanum (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2026)
This study aims to analyze the integration of pedagogical competence and professional competence of Islamic Religious Education (PAI) teachers with inclusive learning strategies in overcoming students’ learning barriers at SMA Negeri 1 Manyak Payed. Inclusive learning is understood as an educational approach that emphasizes the fulfillment of every student’s right to learn through the adjustment of learning methods, media, and evaluation according to students’ individual characteristics and needs. This research employs a qualitative approach with a field research design. The research site is SMA Negeri 1 Manyak Payed, focusing on PAI instruction in class X.1. The research subjects include the school principal, PAI teachers, and students. Data were collected through in-depth interviews, participatory observation, and documentation. Data analysis was conducted interactively through the stages of data reduction, data display, and conclusion drawing, while data validity was ensured through source and method triangulation. The results show that PAI teachers implement inclusive learning strategies through differentiated instruction, the use of adaptive and multisensory learning media, and flexible learning evaluation. Differentiated instruction is carried out by adjusting methods, materials, and assignments based on students’ abilities and needs. The use of visual, audio, and audiovisual media helps students who experience difficulties in reading, memorizing, and understanding PAI material. Learning evaluation does not focus solely on written tests but also employs performance-based assessment and project-based tasks. The integration of pedagogical competence and professional competence of PAI teachers is a crucial factor in creating inclusive and effective learning. Pedagogical competence is reflected in the ability to understand students’ characteristics and manage learning adaptively, while professional competence is evident in deep mastery of PAI subject matter. This study recommends enhancing teacher competence through continuous training and strengthening school policy support to reinforce the implementation of inclusive learning